Оцінка якості трудового потенціалу будівельної організації в умовах ринкових відносин - Рекуненко, С. М.; Гольда, А. В. (Ways to Improve Construction Efficiency, 2012)
The qualitative characteristics of the organization labor potential are considered, and on this basis a coefficient method for assessing the quality of the construction enterprise labor potential.